2017
DOI: 10.1038/srep42670
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategies of the coral Turbinaria reniformis in the northern Gulf of Aqaba (Red Sea)

Abstract: Here we describe for the first time the reproductive biology of the scleractinian coral Turbinaria reniformis studied during three years at the coral reefs of Eilat and Aqaba. We also investigated the possibility of sex change in individually tagged colonies followed over a period of 12 years. T. reniformis was found to be a stable gonochorist (no detected sex change) that reproduces by broadcast spawning 5–6 nights after the full moon of June and July. Spawning was highly synchronized between individuals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Different species possess different tolerances to environmental conditions; for example, corals demonstrate species-specific responses to global warming and subsequent bleaching and mortality (25,34). Throughout the years of this study, some species at the same area still demonstrated well-synchronized spawning, as expected (28,35) (Fig. 1B).…”
Section: Discussionmentioning
confidence: 61%
“…Different species possess different tolerances to environmental conditions; for example, corals demonstrate species-specific responses to global warming and subsequent bleaching and mortality (25,34). Throughout the years of this study, some species at the same area still demonstrated well-synchronized spawning, as expected (28,35) (Fig. 1B).…”
Section: Discussionmentioning
confidence: 61%
“…, Rapuano et al. ). Two species ( A. squarrosa and A. pharaonis ) were also collected from both habitats in 2017.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, shallow samples of M. verrucosa in June 2015 and of A. squarrosa and A. valida in September 2015 were not collected. The four additional species were collected in either 2015 or 2016 from shallow (1-8 m) and mesophotic (44-55 m) habitats approximately one week prior to their expected time of spawning, based on previous studies (Shlesinger and Loya 1985, Shlesinger et al 1998, Rapuano et al 2017. Two species (A. squarrosa and A. pharaonis) were also collected from both habitats in 2017.…”
Section: Study Sites and Sampling Regimementioning
confidence: 99%
“…Some brooder species release their offspring as fertilized eggs or embryos (Vermeij, Sampayo, Bröker, & Bak, 2004) or produce planulae asexually (Ayre & Resing, 1986; Sherman et al., 2006). Although shallow‐water zooxanthellate scleractinians are well known for their synchronized mass‐spawning events triggered by lunar and seasonal periods (Sorek & Levy, 2014), some species reproduce year‐round (e.g., Tubastraea coccinea ; Glynn et al., 2008) or asynchronously for prolonged periods (e.g., Turbinaria reniformis ; Harrison et al., 1984; Rapuano et al., 2017).…”
Section: Introductionmentioning
confidence: 99%